﻿Experimental study of new derivatives of 3-hydroxypyridine as pharmacological agents for the correction of ischemic brain injury after intracerebral hemorrhage - Olesya V. Shcheblykina; Dmitry V. Shcheblykin; Konstantin S. Trunov; Anton P. Danilenko; Vladimir S. Lipatov (Belgorod National Research University, 2022)
Introduction: Limiting the action of secondary injury factors can improve the prognosis in acute cerebral accidents. The aim of the investigation is to study the neuroprotective effects of 3-hydroxypyridine derivatives. Materials and methods: The study was performed in Wistar rats. An intracerebral hemorrhage (ICH) model was used. The animals were once administered intraperitoneally with the test drugs 1 hour before the surgery and on the 1st, 2nd and 3rd days. The registration of behaviors and condition of the animals on days 1, 3, 7 and 14 and the morphological examination of the brain were performed. Results and discussion: The use of the substances LKhT 4-97 and LKhT 11-02 in the treatment of experimental ICH had a positive effect on the survival rate of the animals and on the resolution rate of pathological signs (p<0.05). Clinical observations were confirmed by the results of analysis of the S100b brain damage marker and morphometry. The efficacy of LKhT 3-15 was largely comparable to that of the reference drug Mexidol. The efficacy of LKhT 01-09 was significantly inferior to that of the reference drug Mexidol. Differences in the neuroprotective effects of the studied substances are related to the metabolism of their various pharmacophores. A hypothetical mechanism for the induction of their neuroprotective effects has been proposed. Conclusion: Three of the four 3-hydroxypyridine derivatives under study have a neuroprotective effect, which is manifested in a more rapid resolution of pathological symptoms and less pronounced signs of neurodegeneration.